The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-05018-z
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effects of human footprint, natural features and predation risk best predict seasonal resource selection by white-tailed deer

Abstract: Land modified for human use alters matrix shape and composition and is a leading contributor to global biodiversity loss. It can also play a key role in facilitating range expansion and ecosystem invasion by anthrophilic species, as it can alter food abundance and distribution while also influencing predation risk; the relative roles of these processes are key to habitat selection theory. We researched these relative influences by examining human footprint, natural habitat, and predator occurrence on seasonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 69 publications
2
13
3
Order By: Relevance
“…Mule deer summer occupancy of harvest blocks increased with increasing forest age in the surrounding area, and both white-tailed deer and grizzly bear occupancy increased as the amount of young forest (i.e., harvest blocks <50 years old) in the surrounding area decreased. These results contrast with research in northern Alberta, where the total amount of harvest blocks increased the probability of white-tailed deer presence (Dawe, 2011) and white-tailed deer selected areas closer to harvest blocks (Darlington et al, 2022), but complement research in west-central Alberta, where there was a negative relationship between white-tailed deer abundance and harvest blocks (Nielsen et al, 2017). While we found occupancy of harvest blocks was influenced by the age of the forest surrounding the harvest block, our results did not suggest that occupancy was directly related to the site-specific age of the harvest block.…”
Section: Single-species Occupancycontrasting
confidence: 99%
See 1 more Smart Citation
“…Mule deer summer occupancy of harvest blocks increased with increasing forest age in the surrounding area, and both white-tailed deer and grizzly bear occupancy increased as the amount of young forest (i.e., harvest blocks <50 years old) in the surrounding area decreased. These results contrast with research in northern Alberta, where the total amount of harvest blocks increased the probability of white-tailed deer presence (Dawe, 2011) and white-tailed deer selected areas closer to harvest blocks (Darlington et al, 2022), but complement research in west-central Alberta, where there was a negative relationship between white-tailed deer abundance and harvest blocks (Nielsen et al, 2017). While we found occupancy of harvest blocks was influenced by the age of the forest surrounding the harvest block, our results did not suggest that occupancy was directly related to the site-specific age of the harvest block.…”
Section: Single-species Occupancycontrasting
confidence: 99%
“…Successional stages and timing of succession can vary with local conditions like soil moisture, acidity, and topography (Brulisauer et al, 1996; Hart & Chen, 2006), and harvest block age alone may not be an accurate indicator of available ungulate forage in our study area. While it is frequently suggested that deer select for early seral stands (Darlington et al, 2022; Fisher & Wilkinson, 2005; Toews et al, 2018), our results indicate that use of harvest blocks may be dependent on the availability of forest across a range of successional stages. Others have reported that deer select for uneven‐aged mature forest and large‐scale habitat heterogeneity (Kie et al, 2002; Nielsen et al, 2017; Wallmo & Schoen, 1980), and grizzly bear use of harvest blocks depends on the landscape‐level forest composition (Kearney et al, 2019; Nielsen et al, 2004; Stewart et al, 2012).…”
Section: Discussioncontrasting
confidence: 63%
“…Finally, we note that, unlike locations from satellite collars, helicopter‐based observations are made only in daylight hours during good flying weather, so helicopter samples might be biased in favor of energy‐intake behaviors—moving about and seeking browse—and against energy‐conservation behaviors, bedding down and seeking shelter, as expected at night and in cold, inclement weather. Notwithstanding this possibility, we note that results and conclusions about white‐tailed deer selection are in agreement with those from satellite‐telemetry‐based RSFs studying deer behavior (Darlington et al, 2022) and camera‐trap studies studying landscape‐scale deer distribution (Fisher et al, 2020, 2021; Fisher & Burton, 2020; Fisher & Ladle, 2022) from the same region. Both sampling modes are agnostic to diel period and weather, suggesting that any bias from helicopter observations do not alter conclusions.…”
Section: Discussionsupporting
confidence: 88%
“…Certainly, linkages between winter severity (snow depth, snow hardness, and temperature lows and temperature variability) and response to landscape cover have been observed for white‐tailed deer (Dawe et al, 2014; Dawe & Boutin, 2016; Kennedy‐Slaney et al, 2018), so a region‐specific relationship to conifer is not unexpected. The fact that avoidance of conifer for western boreal deer has been demonstrated via satellite‐collar studies (Darlington et al, 2022) as well as multiple camera‐trap studies (Fisher et al, 2020, 2021; Fisher & Burton, 2020; Fisher & Ladle, 2022) lends credence to our conclusions.…”
Section: Discussionsupporting
confidence: 80%
“…Understanding trade‐offs between attraction to forage and avoidance of predators, and the spatial scales at which they occur, is fundamental to predicting species responses to caribou management actions, such as habitat restoration and predator control. Further investigation of direct measures of forage availability, resource selection, and mortality from predation is warranted for ungulates in this system (Darlington et al, 2022 ; Finnegan et al, 2018 ; McKay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%